A. \(a + b = 16\)
B. \(a + b = 11\)
C. \(a + b = 14\)
D. \(a + b = 13\)
C
Điều kiện \(\left\{ \begin{array}{l}x > 0\\x \ne \frac{1}{2}\end{array} \right.\)
Ta có \({\log _7}\left( {\frac{{4{x^2} - 4x + 1}}{{2x}}} \right) + 4{x^2} + 1 = 6x \Leftrightarrow {\log _7}\left( {\frac{{{{\left( {2x - 1} \right)}^2}}}{{2x}}} \right) + 4{x^2} - 4x + 1 = 2x\)
\( \Leftrightarrow {\log _7}{\left( {2x - 1} \right)^2} + {\left( {2x - 1} \right)^2} = {\log _7}2x + 2x & \left( 1 \right)\)
Xét hàm số \(f\left( t \right) = {\log _7}t + t \Leftrightarrow f'\left( t \right) = \frac{1}{{t\ln 7}} + 1 > 0\) với \(t > 0\)
Vậy hàm số đồng biến
Phương trình (1) có dạng \(f\left( {{{\left( {2x - t} \right)}^2}} \right) = f\left( {2x} \right) \Leftrightarrow {\left( {2x - 1} \right)^2} = 2x \Leftrightarrow \left[ \begin{array}{l}x = \frac{{3 + \sqrt 5 }}{4}\\x = \frac{{3 - \sqrt 5 }}{4}\end{array} \right.\)
Vậy \({x_1} + 2{x_2} = \left[ \begin{array}{l}\frac{{9 - \sqrt 5 }}{4}\left( l \right)\\\frac{{9 + \sqrt 5 }}{4}\left( {tm} \right)\end{array} \right. \Rightarrow a = 9;b = 5 \Rightarrow a + b = 9 + 5 = 14\)
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247